PRINSIP DEKLARATIF PENDAFTARAN HAK CIPTA: Kontradiksi Kaedah Penda Ō aran Ciptaan dengan Asas Kepemilikan Publikasi Pertama Kali - Suyud Margono (Badan Pembinaan Hukum Nasional, 2012)
Hukum Hak Cipta Indonesia memiliki regulasi tentang Penda Ō aran Hak Cipta. Penda Ō arannya bisa dilakukan oleh pemohon baik Pencipta atau Pemegang Hak Cipta ke Direktorat Jenderal Kekayaan Intelektual. Ser Ɵ fi kat Penda Ō aran Hak Cipta menjadi alat buk Ɵ jika terjadi sengketa melalui proses penyelesaian di Pengadilan atau non-pengadilan. Ketentuan Penda Ō aran Ciptaan ini Ɵ dak seimbang dan mengeyampingkan keberadaan karya-karya Cipta yang Ɵ dak dida Ō arkan dalam jumlah jutaan. Sebenarnya, dalam prinsip universal dan perlindungan hak cipta internasional Ɵ dak mewajibkan untuk se Ɵ ap penda Ō aran bagi penciptaan kepada lembaga di satu negara tertentu. Sebuah doktrin universal yang digunakan, untuk perlindungan hak cipta telah mendapat perlindungan hukum setelah dibuat, dan dapat diketahui, didengar, dilihat oleh pihak lain. Prinsip ini dikenal dengan Prinsip Deklara Ɵ f. Ini berar Ɵ ekspresi penciptaan memiliki perlindungan sejak publikasi pertama kalinya. Oleh karena itu, berdasarkan permasalah pertentangan antara Penda Ō aran Hak Cipta dan perlindungan penciptaan yang mengiku Ɵ sistem deklara Ɵ f, maka perlu pemikiran ulang pengaturan penda Ō aran hak cipta yang bertentangan dengan kepemilikan hak cipta yang didapat sejak saat penciptaan pertama dipublikasikan.Indonesian Copyright Law has regula Ɵ on about Copyright Registra Ɵ on. Its registra Ɵ on can be done by applicant(s) even Creator or the Owner of Copyrights to Directorate General Intellectual Property (Indonesia IP O ffi ce). Cer Ɵ fi cate of Creature Registra Ɵ on will make easy proved if dispute happening event takes proceedings at Court or non-court se Ʃ lement. This rule of Copyright Registra Ɵ on made in-balance for the un-register crea Ɵ on in fact a million crea Ɵ on that doesn’t listed in General of registered creature. Actually, in universal principle and based on interna Ɵ onal conven Ɵ on concerning copyright protec Ɵ on not knows or not make compulsory for any sense registra Ɵ on for crea Ɵ on or given authority to the ins Ɵ tu Ɵ on at one par Ɵ cular state. An Universal doctrine that is u Ɵ lized for copyright protec Ɵ on which is a creature has go Ʃ en law protec Ɵ on since that creature fi nish is made, and gets to be known, heard, seen by other Party this principle recognised with Declara Ɵ ve Principal. Its mean a that crea Ɵ on is not an ideas but cons Ɵ tute protected expression of ideas or have protec Ɵ on since fi rst Ɵ me publica Ɵ on, but especially at Indonesia has rule and mechanism of copyrights Registra Ɵ on event its registra Ɵ on is not compulsary. Therefore, based on problema Ɵ c contradic Ɵ ng among Copyright Registra Ɵ on and protec Ɵ on of crea Ɵ on that follow declara Ɵ ve system this research is rethinking the existence copyright registra Ɵ on rule causes to be breached copyright ownership compossed to be go Ʃ en since that crea Ɵ on fi rst Ɵ me is publicized ( fi rst to publish).